2023
DOI: 10.3390/agriculture13051016
|View full text |Cite
|
Sign up to set email alerts
|

Facial Region Analysis for Individual Identification of Cows and Feeding Time Estimation

Abstract: With the increasing number of cows per farmer in Japan, an automatic cow monitoring system is being introduced. One important aspect of such a system is the ability to identify individual cows and estimate their feeding time. In this study, we propose a method for achieving this goal through facial region analysis. We used a YOLO detector to extract the cow head region from video images captured during feeding with the head region cropped as a face region image. The face region image was used for cow identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Individual cow recognition will also be an important part of future research. In both [19,35], they conducted cow identity studies based on cow face patterns and back patterns, respectively, through the improved YOLO model. In future studies, we will explore the performance of the Res-DenseYOLO model on cow identity.…”
Section: Limits and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual cow recognition will also be an important part of future research. In both [19,35], they conducted cow identity studies based on cow face patterns and back patterns, respectively, through the improved YOLO model. In future studies, we will explore the performance of the Res-DenseYOLO model on cow identity.…”
Section: Limits and Future Researchmentioning
confidence: 99%
“…Wang et al [18] optimized anchor box sizes and boundary box loss functions based on the YOLOv3 model to quickly identify estrus behaviors in dairy cows. Kawagoe et al [19] used a YOLO detector to capture cow heads eating from videos and applied transfer learning for detection of cow feeding time. Guo et al [20] used a YOLOv3-tiny model for cow individual identification and used eye temperature recognition technology to measure cow body temperature, realizing non-invasive identification of cow temperature and individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Research on Behavioral Prediction: Kawagoe et al, [50] explored the use of facial recognition technology not just for identification but also for predicting behavioral patterns and health conditions in cows. The research indicated that certain facial features and expressions could be linked to health status, stress levels, and even reproductive cycles [51].…”
Section: Key Studies and Their Findingsmentioning
confidence: 99%